ROA, ROE, and EPS on Stock Prices in The Basic & Chemical Industry Sector Listed on The Jakarta Composite Index - Sonia Krisdayanti (YPPP AL-AMSI, 2021)
This study aims to examine the effect of Return On Assets (ROA), Return On Equity (ROE) and Earning Per Share (EPS) on Stock Prices in Manufacturing Companies in the Basic & Chemical Industry Sector Listed on the Indonesia Stock Exchange (IDX) for the 2015-2019. The sample selection in this study used purposive sampling method. The method used in this research is panel data regression analysis. The results of the research are: Return on Assets (ROA) has no a significant effect on stock prices. This is indicated by the t-count is greater than the t-table value (1.009 < 1.98), with a probability value bigger than the significance or (0.3151 > 0.05), while the Return On Equity (ROE) has no significant effect on the price share. This is indicated by the t-count is smaller than the t-table value (0.849 < 1.98), with a probability value greater than significance or (0.3978 > 0.05), then Earning Per Share (EPS) has a significant effect on stock prices. This is indicated by the t-count is greater than the t-table value (2.16 > 1.98), with a probability value smaller than the significance or (0.0331 < 0.05), and Based on the results of the F test, Return On Assets (ROA), Return On Equity (ROE) and Earning Per Share (EPS) together have a significant effect on stock prices. This is indicated by the F-count value is greater than the F-table (27.61 > 2.63), and the probability value is also smaller than the 0.05 significance level (0.0000 < 0.05).